Nail changes in systemic diseases - Mojakgomo H. Motswaledi; M.C. Mayayise (South African Family Practice)
Discerning between actual nail conditions and nail changes associated with systemic disease is a very important and interesting part of any clinical examination. This article provides a helpful clinical atlas of nail changes that may be associated with systemic disease and will assist the clinician to identify and verify these clinical signs. The article includes information on common nail changes like koilonychia, longitudinal and transverse grooves, nail pitting, clubbing, pincer nails, pterygia, splinter haemorrhages, nicotine-stained nails, cyanosis, jaundice and brittle nails. It also includes information on the -nychias (micro-, macro-, leuko-, pachy-, melano- and dyschromo-), onycholysis and onychoschizia, red lunulas, yellow nail syndrome, Muehrcke’s white bands, Terry’s nails and periungual fibromas (Koenen tumours).